IN-LINE PHYSICAL DESORPTION UNIT: MODELLING, DESIGN AND OPTIMISATION - BAN , ZHEN HONG (2015)
C02 removal from natural gas stream is crucial as there are a number of high C02 concentration gas reservoirs in the world. Physical absorption process can be utilised to remove C02 since the feed pressure of natural gas stream is relatively high. However, the excessive footprint of the flash drum has greatly reduced the feasibility for the physical absorption process to be employed at offshore condition. Therefore, a compact in-line physical desorption unit would be designed via numerical modelling approach in current work. However, most of the available numerical modelling approach are not suitable to model the desorption phenomenon. In current work, the bubble nucleation and growth models were integrated with Computational Fluid Dynamics - Population Balance Model (CFD - PBM) to model the non-equilibrium desorption phenomenon. The bubble nucleation and growth models were written as user-defined function (UDF).